Catering to Inclusion and Diversity With Universal Design for Learning in Asynchronous Online Education: A Self-Determination Theory Perspective - Ismailov, Murod; Chiu, Thomas K. F. (Frontiers in Psychology, 2022)
The Universal Design for Learning (UDL) guidelines were extensively studied to understand inclusive learning and teaching in higher education. However, to date, there have been few studies that approached UDL-based asynchronous university courses from the needs satisfaction perspective in self-determination theory (SDT). To address this gap, researchers designed and implemented two 15-week asynchronous online courses based on UDL. They then tested their effectiveness with college freshmen (N = 225) by adopting a sequential explanatory mixed method. The study aimed to examine (i) whether asynchronous instruction based on UDL catered to inclusion and diversity across gender and academic background and (ii) whether the instructional design supported learner engagement and needs satisfaction. The findings showed that both male and female students as well as Arts and Sciences students equally engaged in the courses and perceived the needs support from the course design. However, the study also found that although universal design supported autonomy and competence, it nonetheless failed to fully satisfy learners’ relatedness needs. The researchers concluded by discussing empirical and theoretical implications.